Pathogenesis and genetics of celiac disease; a systematic review - Alireza Ahmadzadeh; Mostafa Rezaei-Tavirani (Egyptian Journal of Medical Human Genetics)
Abstract Introduction Celiac disease is an autoimmune disorder characterized by enteropathy and systemic manifestations, triggered by the ingestion of gluten. The incidence of this disease is on the rise. This paper presents an overview of the epidemiology, diagnostic criteria, and pathological aspects of celiac disease. Furthermore, we provide a summary of the key genes associated with this disorder. Methods In this systematic review, a comprehensive search from the years 2000 to 2024 was conducted across major databases such as PubMed, Scopus, and Google Scholar to identify studies related to celiac disease, utilizing relevant keywords. Studies that did not pertain to celiac disease were systematically excluded from consideration. Results According to a review of 63 studies, celiac disease is an immune mediated disorder that is triggered by the consumption of gluten in genetically predisposed individuals; however intestinal microbiota and genetic influences, significantly contribute to the disease’s development. The genetic foundation of celiac disease is robust. Strong associations between this disease and HLA DQ2, DQ8, and over 100 non-HLA genes have been identified. Conclusion Celiac disease is rooted in genetic factors. Understanding these genetic underpinnings enhances our comprehension of the disease mechanisms, thereby facilitating the development of novel treatment strategies and preventive interventions.